2013
DOI: 10.1080/11263504.2013.770808
|View full text |Cite
|
Sign up to set email alerts
|

The ecological adaptability of four typical plants during the early successional stage of a tropical rainforest

Abstract: PLEASE SCROLL DOWN FOR ARTICLETaylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. However, Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Any opinions and views expressed in this publication are the opinions and views of the authors, and are not the views of or endorsed by Taylor & Francis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Light and CO 2 curves reflect how plant physiological functions respond to transient environmental changes (Shi et al, 2006). The maximum photosynthetic rate of species may suffer from depression in different degrees under higher irradiance (Mao et al, 2014). Studies have demonstrated that plants obtain the maximum photosynthesis by optimizing resource allocation between RuBisCo and chlorophyll to maintain a balance between Vcmax and Jmax (Wilson et al, 2000).…”
Section: Change Of Photosynthetic Parametersmentioning
confidence: 99%
“…Light and CO 2 curves reflect how plant physiological functions respond to transient environmental changes (Shi et al, 2006). The maximum photosynthetic rate of species may suffer from depression in different degrees under higher irradiance (Mao et al, 2014). Studies have demonstrated that plants obtain the maximum photosynthesis by optimizing resource allocation between RuBisCo and chlorophyll to maintain a balance between Vcmax and Jmax (Wilson et al, 2000).…”
Section: Change Of Photosynthetic Parametersmentioning
confidence: 99%
“…The ability of expansive plants to expand in a community is dependent on several direct and indirect interactions between the species and their environment and other species (Pyšek et al, 2004;Simberloff, 2010;Kelbel & Adamčíková, 2011). The strength and direction of these species interactions are context dependent, and their outcomes depend on several factors such as resource supply, physical stress, disturbance, competitive ability and life history stage (Chesson, 2000;Mao et al, 2014). These factors influence the relative competitive ability of species in acquiring resources and influence the required conditions for expansive species to find successful niches (Kraaij & Ward, 2006).…”
Section: Introductionmentioning
confidence: 99%